Perspective of Immunopathogenesis and Immunotherapies for Kawasaki Disease - Chang, Lung; Yang, Horng-Woei; Lin, Tang-Yu; Yang, Kuender D. (Frontiers in Pediatrics, 2021)
Kawasaki Disease (KD) is an acute inflammatory illness that mostly occurs in children below five years of age, with intractable fever, mucocutaneous lesions, lymphadenopathy, and lesions of the coronary artery (CAL). KD is sharing clinical symptoms with systemic inflammatory syndrome in children (MIS-C) which is related to COVID-19. Certain genes are identified to be associated with KD, but the findings usually differ between countries and races. Human Leukocyte Antigen (HLA) allele types and toll-like receptor (TLR) expression are also correlated to KD. The acute hyperinflammation in KD is mediated by an imbalance between augmented T helper 17 (Th17)/Th1 responses with high levels of interleukin (IL)-6, IL-10, IL-17A, IFN- and IP-10, in contrast to reduced Th2/Treg responses with lower IL-4, IL-5, FoxP3 and TGF- expression. KD has varying phenotypic variations regarding age, gender, intravenous immunoglobulin (IVIG) resistance, macrophage activation and shock syndrome. The signs of macrophage activation syndrome (MAS) can be interpreted as hyperferritinemia and thrombocytopenia contradictory to thrombocytosis in typical KD; the signs of KD with shock syndrome (KDSS) can be interpreted as overproduction of nitric oxide (NO) and coagulopathy. For over five decades, IVIG and aspirin are the standard treatment for KD. However, some KD patients are refractory to IVIG required additional medications against inflammation. Further studies are proposed to delineate the immunopathogenesis of IVIG-resistance and KDSS, to identify high risk patients with genetic susceptibility, and to develop an ideal treatment regimen, such as by providing idiotypic immunoglobulins to curb cytokine storms, NO overproduction, and the epigenetic induction of Treg function.